Information Systems: Process and Practice - Urquhart, Christine; Hamad, Faten; Tbaishat, Dina; Yeoman, Alison (iResearch Series, 2017)
This book adopts a holistic interpretation of information architecture, to offer libraries and information professionals a variety of methods, tools, and techniques that may be used when designing websites and information systems that support workflows and what people require when "managing information".